Investment Arbitration under the Spotlight - What next for Asia - Nariman, Fali (Institutional Knowledge at Singapore Management University, 2014)
This lecture will provide an analysis of recent developments in investment arbitration in Asia with a particular focus on the role played by bilateral and multilateral agreements in the region. A number of countries, particularly in South-East Asia and South Asia have engaged in investment arbitration in the last couple of years. Indonesia has reportedly signaled its intention to terminate its bilateral investment treaties, following the example of several Latin American countries in recent years. Will India also act on its stated intention to whittle down arbitration protections afforded to investors under Bilateral Investment Treaties? Will other states in the region, known to view these treaties with growing skepticism, follow? Do the dispute resolution mechanisms provided in multilateral investment treaties and free trade agreements now represent the preferred method for protection of overseas investors? Will the growing tide of discontent with ISDS and the recent decision to award US$50 billion to Yukos in proceedings against Russia have any impact on investment arbitration in Asia? How do these developments impact the inherent tension between Investment Arbitration and Sovereignty? Mr Fali Nariman, a preeminent senior advocate from India and a frequent investment treaty arbitrator, will, with the wisdom of his experience in the field, discuss these and other related issues in the 2014 edition of the HSF-SMU Arbitration Lecture.